60-jarig bestaan. Receptie in Krasnapolsky. Eventueel foto tijdens congres op 17 en 18 juni gemaakt
60-jarig bestaan. Receptie in Krasnapolsky. Eventueel foto tijdens congres op 17 en 18 juni gemaakt.